THE PRODUCTION OF ALKYL POLYGLYCOSIDE (APG) SURFACTANT AND ITS APPLICATION IN LIQUID HAND SOAP - Siti Aisyah, Ani Suryani, Titi Candra Sunarti (Department of Agroindustrial Technology, Bogor Agricultural University, 2010)
ABSTRACT Alkyl polyglycoside (APG) is one of nonionic surfactant that is applied in some formulations such as personal care products, cosmetics, textile bleachies and herbicides. APG’s production is carried out in two stages, i.e. butanolysis and transacetalization. These processes are then followed by neutralization, distillation, dissolution and bleaching. This research aims were to study the influence of fatty alcohol C10 (decanol) and C12 (dodekanol) and the activator material, and to characterize the APG. Beside that, the research studied about the characteristics of liquid hand soap with the APG as the raw material. The synthesized APG had characteristics as follow: bright-yellow to brown-black in color, with percent of transmittance value range of 12.99-55.91%. The yield obtained was 37.44-46.88%. The abilities to reduce surface tension were 59.90-64.10%; the ability to reduce interfacial tension were 90.69-94.25%, and emulsion stability of 65.24-80.49% in 5 hours. Compared to commercial APG, the ability to reduce surface tension was 55.97%, the ability to reduce interfacial tension was 91.63%, and emulsion stability of 66.46-70.73%. The best APG formulation had HLB value of 8.498. Liquid soap produced using APG which is obtained previously has cleaning power as good as 128 FTU turbidity, specific gravity of 1.024 g/ml, pH of 6.98 and free of microbial contamination. While commercial liquid hand soap had the following characteristics: cleaning power of 192 FTU turbidity, specific gravity of 1.027 g/ml, pH of 7.03, and free of microbial contamination. Organoleptic test on the aroma, colour, and impression after the use of liquid hand soap formulation showed that in general, panelists preferred the best formulation of liquid hand soap. While on foam and viscosity properties, panelists preferred the commercial hand wash liquid soap of brand “D”. Keywords: fatty alcohol, liquid hand soap, APG